Temporal Variation of the Profile and Concentrations of Paralytic Shellfish Toxins and Tetrodotoxin in the Scallop, Patinopecten yessoensis, Cultured in a Bay of East Japan - Satoshi Numano (Marine Drugs, 2019)
Paralytic shellfish toxins (PSTs) are the major neurotoxic contaminants of edible bivalves in Japan. Tetrodotoxin (TTX) was recently detected in bivalve shellfish around the world, drawing widespread attention. In Japan, high levels of TTX were reported in the digestive gland of the scallop, Patinopecten yessoensis, in 1993; however, no new data have emerged since then. In this study, we simultaneously analyzed PSTs and TTX in scallops cultured in a bay of east Japan using hydrophilic interaction chromatography (HILIC)-MS/MS. These scallops were temporally collected from April to December 2017. The highest concentration of PSTs (182 µmol/kg, total congeners) in the hepatopancreas was detected in samples collected on May 23, lined to the cell density of the dinoflagellate, Alexandrium tamarense, in seawater around the scallops, whereas the highest concentration of TTX (421 nmol/kg) was detected in samples collected on August 22. Contrary to the previous report, temporal variation of the PSTs and TTX concentrations did not coincide. The highest concentration of TTX in the entire edible tissues was 7.3 µg/kg (23 nmol/kg) in samples obtained on August 22, which was lower than the European Food Safety Authority (EFSA)-proposed threshold, 44 µg TTX equivalents/kg shellfish meat. In addition, 12β-deoxygonyautoxin 3 was firstly identified in scallops.